Study of climate change impact on hydro-climatic extremes in the Hanjiang River basin, China, using CORDEX-EAS data - Dai, C. (2023)
An integrated assessment modelling framework is introduced to comprehensively evaluate the climate change impact on hydro-climatic extremes over the Hanjiang River basin, China. The framework consists of climate model scenarios, bias correction method, hydrological model, and extreme climate and streamflow indices. The outputs from five CORDEX-EAS regional climate models (RCMs) under RCP 2.6 and 8.5 were firstly bias-corrected for two future windows, i.e. near future (2021-2050) and far future (2051-2080), and then used to drive a hydrological model to estimate the changes of extreme climate and streamflow, which were described by 19 standard hydro-climatic indices. The hydrological model was calibrated using a new software developed based on generalized likelihood uncertainty estimation (GLUE) algorithm under parallel computing environment. From the ensemble median of RCMs, it was found that the study basin is expected to be slightly wetter and significantly hotter in the future, with more intense and frequent precipitation and higher temperature extremes. Particularly, the extreme annual maximum 1-day streamflow index would have an overall increase across the basin, with the most significant increase in the south-western part of the basin. The extreme annual minimum 7-day streamflow index is projected to have a significant increase in the northern, south-western and south-eastern parts of the basin in the near future, while it would show a basin-wide decrease in the far future under RCP 8.5. Our findings helped gain an in-depth insight into the responses of hydro-climatic extremes to climate changes for a large-scale watershed and offer valuable guidance to decision makers who are responsible in designing adaptation strategies to mitigate the risks from extreme water-related disasters in the future.